Evaluation of Heavy Metals Found in Vegetables of Some Poultry Farms in Osun State, Nigeria - Ogunwale, Taiwo Olusegun; Oyekunle, John Adekunle O.; Ogunfowokan, Aderemi Okunola; Oyetola, Simoen Oyesoji (Industrial and Domestic Waste Management, 2022)
Heavy metals are persistent in the ecosystem and are held responsible for natural accumulation at all feeding levels. Nevertheless, contact does not occur just because of the availability of a contaminant material in the ecosystem. This present work was aimed at evaluating the contents of heavy metals in vegetables sampled from some poultry farms in Osun State. Five vegetables, namely green vegetable, bitter leaf, gruty-stalked jatropha, scent leaf, and water leaf, were tested for heavy metals, such as arsenic, cadmium, copper, iron, lead, and zinc, using a flame atomic absorption spectrophotometer following wet digestion with HNO3. Quality assurance techniques included blank testing, recovery testing, and calibration of concentrations. Descriptive statistics were used for data interpretation. The analytical results signified that those heavy metals were detected in all the vegetables from the various sites. Most of the contents are below the Food and Agriculture Organization/World Health Organization safe range in the vegetable section, with the exception of A. Drastic measures should be adopted to avoid the use of such health-toxic contents of metals in poultry feed. So, it was suggested that there should be constant monitoring of poultry sites to control, limit, and stop heavy metal contamination once and for all.